Characterizing the background in tt events with a J/ψ → µ −µ + in proton-proton collisions at √ s = 13 TeV using the ATLAS detector - Barends, Kevin Nicholas (Department of Physics, 2020)
So far, various measurements have been performed for the top quark mass using jets as a dominant experimental signature. The leading precision measurement of 1732.44 ±0.13±0.47 GeV is a combination of top quark mass measurements conducted by the CMS collaboration. However, these various measurements suffered from large jet reconstruction uncertainties. This study looked at a different experimental signature involving a lepton and J/ψ such that the top quark decay mode is t → W (→ lν)b (→ J/ψ [→ µ +µ −]+X). This signature combines the kinematics of the three leptons in the final state and therefore, is not significantly dependent on the reconstructed kinematics of the jets. The statistical uncertainty in the top mass measurement was determined from the invariant mass of the lepton and J/ψ distribution through a template morphing maximum likelihood method, giving a value of 2.9 GeV. This signature comes with background contributions from non-prompt and mis-reconstructed leptons and from selecting J/ψ mesons which did not originate from top quark B-hadron decays. The background contribution from non-prompt and mis-reconstructed leptons was determined to be overestimated in the muon channel but more accurately estimated in the electron channel in the signal region. This background lepton contribution was determined using the common methodology by the ATLAS experiment. The background contribution from J/ψ mesons was determined by applying a two-dimensional fit on the mass and pseudo-proper time of the J/ψ. These background contributions were reduced by applying a tighter selection cut on the J/ψ mass and including an additional selection cut on the pseudo-proper time of the J/ψ mesons. These cuts improved the signal contribution but, due to limited statistics, could not be shown to improve the uncertainty in the mass measurement.